2018
DOI: 10.33549/physiolres.933754
|View full text |Cite
|
Sign up to set email alerts
|

Plethysmographic and Biochemical Markers in the Diagnosis of Endothelial Dysfunction in Pediatric Acute Lymphoblastic Leukemia Survivors – New Applications

Abstract: Acute lymphoblastic leukemia (ALL) and its treatment are associated with endothelial dysfunction (ED) and increased cardiovascular risk in adulthood. There are no data on ED in children after successful treatment of ALL. We aimed to assess new ED in these children using the plethysmographic reactive hyperemia index (RHI) and biomarkers that are known to be related to ED. In all, 22 children (mean 15.6 years), after successful treatment of ALL, and 18 healthy subjects were included in this prospective study. RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…For example, asymmetric dimethylarginine (ADMA) is a competitive inhibitor of NO synthase and is increased in patients with ALL. ADMA is a product of tumor cell degradation, oxidative stress, manifestation of liver failure and inflammation of the endothelial wall [5,8,9]. It should be noted that there are a number of scientific studies on the levels of nitric oxide in ALL, which have shown the results of increasing total NO [7,14,15].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, asymmetric dimethylarginine (ADMA) is a competitive inhibitor of NO synthase and is increased in patients with ALL. ADMA is a product of tumor cell degradation, oxidative stress, manifestation of liver failure and inflammation of the endothelial wall [5,8,9]. It should be noted that there are a number of scientific studies on the levels of nitric oxide in ALL, which have shown the results of increasing total NO [7,14,15].…”
Section: Resultsmentioning
confidence: 99%
“…reached normal values. This is evidently due to the normalization of a number of NO synthetase inhibitors in children in remission [8] and the absence of pathological factors (remission of leukemia, end of treatment). It should be emphasized that children who received anthracycline drugs are at risk of cardiovascular disease even after therapy [6,9,17].…”
Section: Table 3 Correlation Relationships Between Endothelial Dysfunmentioning
confidence: 99%
See 3 more Smart Citations